DAMPAK PROGRAM PEMBERDAYAAN TERHADAP KESEJAHTERAAN MASYARAKAT DESA (Studi di Desa Mokong Kecamatan Moyo Hulu) - Wati, Jasna; Rampi, Afrijal Jibran; Fiana, Sahrany Defi; Maulana, Akbar Agil (Pusat Riset dan Publikasi, 2025)
Village community empowerment is an effort to develop community independence and well-being by improving knowledge, attitudes, skills, behaviors, abilities, awareness, and utilizing resources through the establishment of policies, programs, activities, and mentoring that align with the essence of the problems and priority needs of the village community. Village communities, especially in areas with abundant natural resources, have the potential to be empowered to improve their welfare. Therefore, this study will analyze the impact of empowerment programs on community welfare which is reviewed through three programs, namely Madu Olat Mokong (Maong), Badan Usaha Milik Desa (BUMDes), and Beragam, Bergizi, Seimbang, dan Aman (B2SA). This research employed a qualitative approach. Data collection was conducted using observation, interviews, and documentation. The research subjects were the Village Government and the community of Mokong Village, Moyo Hulu Sub-District, as implementers and beneficiaries of the empowerment program. The data analysis used was qualitative analysis, with the following steps: data collection, data reduction, data display, and conclusion drawing. The results of this study indicate the impact of community empowerment in Mokong Village, Moyo Hulu Sub-District had a positive impact on community welfare. Overall, the three community empowerment programs in Mokong Village, namely the Maong, BUMDes, and B2SA Program have demonstrated positive synergy in increasing income, community participation, and the quality of life for villagers. However, there are still obstacles faced in implementing the program, so an appropriate strategy is needed to overcome these obstacles to maintain the sustainability of the program.